Максим Рильський як теоретик перекладу - Руда, Т. (Народна творчість та етнографія, 2005)
Maxims Rylsky heritage organically unites the qualities of the scholar and poet, translator and the theorist of the translations. He did translations of the poetry beginning from the 1920th until the last day of his life. The translations became for him a dialog between him and an author. His personal experience in the translation work gave him the right to create his own theory on translations, to write a set of article on the subject: "What is a good translation?" For M. Rylsky translations its first of all an artistic, creative work, he dines the theses about the impossibility of translation from some languages into others. A big amount of translations done from Slavic languages gave him the necessary material for the description of the general problems of translation process. All of these moments are described in this article.